The Role Of Leadership Principles In Increasing Teacher Performance At Tsanawiyah Negeri 1 Madrasah, Kutai Kartanegara Regency - Zainuddin, Nasruddin; Palinggi, Yonathan; Made Agung Dwijatenaya, Ida Bagus (Journal of World Science, 2022)
Introduction: Efforts to improve teacher performance are influenced by the leadership of school principals in carrying out their duties and responsibilities as leaders in schools. The principal is responsible for managing school resources, especially those related to human resources, such as education staff. Madrasah Tsanawiyah Negeri 1 Kutai Kartanegara Regency. Methods: The method used in this research is a qualitative field research method. Data collection tools using documentation, interviews, and observations. The technique of guaranteeing the validity of the data uses triangulation. Results: Based on the results of the study, it is known that the leadership role of the principal in improving teacher performance at Madrasah Tsanawiyah Negeri 1 Kutai Kartanegara Regency is carried out in the form of responding to the school's vision and mission, instructions or information regarding teacher duties, giving encouragement and commitment to teaching duties, increasing professionalism teachers, supervision in improving teacher performance. Madrasah teachers show good performance in aspects of learning planning and aspects of classroom management. While in the aspect of using methods, media, and learning resources, teachers' performance, in this case, still needs to improve because they are less creative in using learning methods and media that encourage students to learn actively. Conclusion: Based on the results of the research and discussion that have been described, it can be concluded as follows: The role of principal leadership in improving teacher performance at Madrasah Tsanawiyah Negeri 1 Kutai Kartanegara Regency, teacher performance, inhibiting factors, and supporting factors for the role of principal leadership in improving teacher performance at Madrasah Tsanawiyah Negeri